CATASTROPHIC ANTIPHOSPHOLIPID SYNDROME AND POSTERIOR OCULAR INVOLVEMENT: Case Series of 11 Patients and Literature Review. Issue 11 (November 2021) - Morel, Nathalie; Bonnet, Clémence; Mehawej, Hanane; Le Guern, Véronique; Pérard, Laurent; Roumier, Mathilde; Brezin, Antoine; Godeau, Bertrand; Haroche, Julien; Benhamou, Ygal; Lambert, Marc; Yelnik, Cécile M.; et al.
Abstract : Purpose: To describe the posterior ophthalmic manifestations of catastrophic antiphospholipid syndrome. Methods: Retrospective case series of patients presenting with catastrophic antiphospholipid syndrome and posterior segment ocular manifestations. The main outcomes were the type of posterior segment manifestations at catastrophic antiphospholipid syndrome diagnosis, specifically retinal vascular occlusion, vasculitis, or choroidopathy, and the final best-corrected visual acuity. Results: This study included 23 patients (11 cases treated by the authors and 12 published case reports); 21 (91%) of them female. Their median age at diagnosis was 28 years (range, 16–79 years). Ophthalmologic manifestations were usually bilateral (n = 19, 83%) and involved vascular occlusive retinopathy (n = 17, 74%), choroidopathy (n = 11, 48%), or retinal vasculitis (n = 1, 4%). Final best-corrected visual acuity was not significantly worse than the best-corrected visual acuity at diagnosis ( P = 0.16). Retinal vascular occlusions were associated with poorer final visual acuity than choroidopathy ( P = 0.002). After a median follow-up of 14 months (range, 2–132 months), nearly half the patients (n = 11, 48%) had permanent vision loss including best-corrected visual acuity of <20/400 for 4 patients. Conclusion: Posterior ophthalmic manifestations of catastrophic antiphospholipid syndrome were mainly bilateral retinal vascular occlusion, which had the worst visual prognosis, followed by choroidopathy and retinal vasculitis. Permanent visual loss was common. Abstract : Posterior ophthalmic manifestations of catastrophic antiphospholipid syndrome in our registry were mainly bilateral retinal vascular occlusion inducing permanent severe visual impairment. Systematic ophthalmic examination of patients with catastrophic antiphospholipid syndrome may enable the detection of early signs of vascular occlusion.